THE INFLUENCE OF INTERNAL CONTROL TOWARD PUBLIC SERVICES OF BPJS KESEHATAN (SURVEY AT PRATAMA MEDIKA CLINIC, ANTAPANI, BANDUNG) - Bunga Indah Bayunitri; Vidia Flavia Oktazafira (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
This research aims to examine the influence of internal control toward public service of BPJS Kesehatan. This research uses quantitative research methods with the object of research is health workers at Medika Pratama Clinic, Antapani, Bandung. The sampling technique used in this research was saturated sampling technique. The result of this research that ????account 4,799 is greater than ????????????????l???? 2,037 with significance rate is 0,05. This means that H0 rejected and H1 accepted, its means that the internal control variable has an influence on public service of BPJS Kesehatan.